2012
DOI: 10.5817/gvms2012-1-2-125
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Report on the New Findings of Mississippian Trilobites in the Březina Formation (Moravian Karst, Czech Republic)

Abstract: New fossiliferous layers of the Březina

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
11
0
Order By: Relevance
“…Recent revision of High-resolution biostratigraphy of the Tournaisian-Visean (Mississippian) boundary interval in the Mokrá quarry by Kalvoda et al (2009) has shown the stratigraphic importance of this fauna. revised the trilobite association from the quarry for the first time and Weiner et al (2012) published a preliminary report on a trilobite occurrence from the Říčka Valley. New discoveries of trilobites from the village of Březina have enriched our knowledge of their stratigraphic importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent revision of High-resolution biostratigraphy of the Tournaisian-Visean (Mississippian) boundary interval in the Mokrá quarry by Kalvoda et al (2009) has shown the stratigraphic importance of this fauna. revised the trilobite association from the quarry for the first time and Weiner et al (2012) published a preliminary report on a trilobite occurrence from the Říčka Valley. New discoveries of trilobites from the village of Březina have enriched our knowledge of their stratigraphic importance.…”
Section: Introductionmentioning
confidence: 99%
“…species from the lower part of the Viséan (= Lower to Middle Viséan, ?or up to the lowermost Upper Viséan, cu IIγ-δ stage, see Fig. 1E) have only been described from the aleuropelitic facies of the Březina Formation (Chlupáč 1966(Chlupáč , 1969Kalvoda et al 2010;Weiner et al 2012;Rak et al 2014). In this paper, the first lower Viséan trilobite association from limestone facies of the Líšeň Formation is described and discussed.…”
mentioning
confidence: 80%
“…This species is associated with further taxa, such as smalleyed archegonids and blind weaniine trilobite Combewoodia (or formerly cystispinine, Hahn et al 2007 andHahn 2018). These associations are characterised by blind or smalleyed taxa (similarity with atheloptic assemblage sensu Fortey & Owens 1987; see Weiner et al 2012, Rak et al 2014. Another lower Viséan trilobite association from the shale successions of the Březina Formation was recorded in the valley of the Říčka brook near BrnoLíšeň, where somewhat largereyed archegonids [Archegonus (Phillibole) cf.…”
Section: Comparison With Other Lower Carboniferous Trilobite Associations From Moraviamentioning
confidence: 99%
See 2 more Smart Citations